Pengaruh Permainan Edukatif Abjad Fishing terhadap Kemampuan Mengenal Huruf Pada Anak Kelompok A di TK Aisyiyah Bustanul Athfal VII Kelurahan Wongkaditi Kecamatan Kota Utara Kota Gorontalo - Mutiara Abdullah; Mohamad Zubaidi; Nunung Suryana Jamin (Inovasi Pendidikan dan Anak Usia Dini, 2024)
This study aims to examine the effect of the Alphabet Fishing educational game on letter recognition ability in Group A children at Aisyiyah Bustanul Athfal VII Kindergarten, Wongkaditi Village, Kota Utara District, Gorontalo City. This research adopted a quantitative approach with a one-group pretest-posttest experimental design. Sampling was conducted through purposive sampling, and data collection methods included tests and observation, whereby children's letter recognition ability was assessed before and after applying the Alphabet Fishing educational game as a treatment. The instrument used in this study to measure letter recognition ability based on two indicators. The subjects were children aged 4-5 years, with a sample size of 20 children. Data analysis results showed a significant increase in children's letter recognition ability after using the Alphabet Fishing educational game. The t-test results showed a significance value of 0.000 with α = 0.05. Since the significance value is smaller than α (0.000 < 0.05), the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted. Therefore, it can be concluded that the Alphabet Fishing educational game positively affects children's letter recognition ability and can be used as an effective learning method in early childhood education.